The impact of air pollution to obesity - Simkova, Simona; Veleminsky, Milos; Sram, Radim J (Neuro endocrinology letters, 2020)
BACKGROUD: Air pollution in ambient air could affect the increase of obesity in children. METHOD: Review analyze papers about the effect of polycyclic aromatic hydrocarbons (PAHs), fine particles (particulate matter < 2.5 μm, PM2.5), and traffic air pollution (NO2, NOx, PM2.5). RESULTS: Prenatal exposure to concentrations 1.73-3.07 ng/m3 PAHs significantly increased obesity at age 5 and 7 years, up to 11 years. All studies indicate the significance of prenatal exposure with concentration > 0.3 ng/m3 of B[a]P (benzo[a]pyrene). Prenatal exposure to PM2.5 above concentrations 10.6-11.9 μg/m3 increased obesity in children up to the age of 9 years. Traffic air pollution was evaluated according to exposure to NO2 and PM2.5. Concentrations NO2 higher 30 μg/m3 affect adiponectin levels in cord blood, cholesterol metabolism, and therefore increase later the risk of overweight or obesity. PM2.5 9.2-11.6 μg/m3 during pregnancy affect adiponectin. These concentrations from the traffic air pollution can affect the metabolism in newborns later related to obesity. CONCLUSION: All these studies indicate that contemporary concentrations of PAHs, PM2.5 and NO2 in ambient air, especially during prenatal period, affect overweight and obesity in children.
Keywords: obezita dětí a dospívajících; Female; Traffic-Related Pollution; Infant; dítě; předškolní dítě; novorozenec; ženské pohlaví; Adolescent; znečištění ovzduší; lidé; Air Pollution; Infant, Newborn; těhotenství; zpožděný efekt prenatální expozice; Particulate Matter; Humans; Male; Air Pollutants; kojenec; polycyklické aromatické uhlovodíky; Child, Preschool; Polycyclic Aromatic Hydrocarbons; Prenatal Exposure Delayed Effects; vystavení vlivu životního prostředí; Child; znečištění spojené s dopravou; mužské pohlaví; Pregnancy; látky znečišťující vzduch; Environmental Exposure; mladiství; Pediatric Obesity; pevné částice